Oral retention of thermally denatured whey protein: In vivo measurement and structural observations by CD and NMR. (16th April 2022) - Bull, Stephanie P.; Khutoryanskiy, Vitaliy V.; Parker, Jane K.; Faka, Marianthi; Methven, Lisa
Highlights: Heating time increases oral retention of whey protein up to 1 min post-consumption. Heating whey protein concentrate increases free thiol concentration. Heating changes secondary and tertiary structures of whey protein concentrate. Circular dichroism found protein unfolding and changes to β-barrel with heating. Nuclear magnetic resonance found heating leads to hydrophobic group exposure. Abstract: This study investigated structural changes and the in vivo retention in the oral cavity of heated whey protein concentrate (WPC). Heated WPC was shown to have both a higher retention time in the oral cavity compared to unheated whey protein up to 1 min post swallow, and a concomitant increase in free thiol concentration. Nuclear magnetic resonance and circular dichroism demonstrated structural changes in the secondary and tertiary structures of the WPC upon heating. Structural loss of the β-barrel was shown to increase during heating, leading to the exposure of hydrophobic regions. The increase in free thiols and hydrophobic regions are two factors which are known to increase mucoadhesive strength and hence increase oral retention of heated whey protein which may subsequently increase the perception of mouthdrying.